Correlating bark thickness and girth of some medicinal trees - Fasola, Taiye R; Olagunju, BO; Robert, ABC (International Journal of Environment, 2014)
Tree barks are continually used and sold for medicinal purposes in Nigerian markets. Incessant debarking of trees, particularly the young trees by bark harvesters poses danger on the growth and survival of the plants. As it cannot be ascertained if the harvested tree barks marketed in large numbers are from older or younger trees, the study aimed at providing solution to this problem. As Diameter at Breast Height (DBH) usually reflects the age of a tree, correlation between bark thickness and DBH was attempted with their various uses. Measurements of bark thickness at breast height and DBH of 69 medicinal tree species belonging to nineteen different families were carried out in various locations in the University of Ibadan campus, Ibadan, Nigeria. The findings subjected to correlation analysis had a positive correlation between the thickness of tree barks and tree girth at breast height. The confirmed knowledge of a positive correlation between tree bark thickness and girth of tree plant is necessary to determine if the barks sold in major markets for ethnomedicinal purposes are harvested from older or younger trees. The medicinal values of the tree barks as antimarial, purgative, haematinic and antimicrobial among other uses were discussed. DOI: http://dx.doi.org/10.3126/ije.v3i2.10642 International Journal of the Environment Vol.3(2) 2014: 287-301